AURUM VITAE: PERANCANGAN KOLEKSI READY-TO-WEAR DELUXE BERNARASI ‘POSITIVE AGING’ - Verena Fedora Goenawan; Andi Hamzah; Wenny Natalia (BAJU: Journal of Fashion and Textile Design Unesa, 2025)
AURUM VITAE is a women’s ready-to-wear deluxe fashion collection, designed based on the theme of the positive side of aging. In a modern society that often views aging negatively, this collection serves as a narrative counterpoint through an elegant and meaningful design approach. The garments are crafted to be timeless, transcending trends. Aging is perceived as the growth of experience, maturity, and a source of deeper meaning in life. The collection features A-line and I-line silhouettes, symbolizing growth and serenity. A neutral color palette — including white, ivory, beige, grey, and taupe — reinforces a sense of calm, elegance, and stability. Fabric manipulation techniques such as pleating, quilting, and broken needle stitching are employed to visually represent the philosophical values of aging, such as accumulated experience. This collection targets women aged 40–50 living in major Indonesian cities, such as Jakarta, who value high-quality clothing with meaningful design and timeless elegance.